TAX DISTANCE LEARNING ANXIETY AND SATISFACTION LEVEL DURING THE COVID-19 PANDEMIC: GENDER AND GRADE DIFFERENCES - Priandhita Sukowidyanti Asmoro; Nurlita Sukma Alfandia; Nurlita Novianti (Universitas Brawijaya, 2022)
The Covid-19 pandemic has forced taxation study programs to adopt distance learning suddenly and without preparation to replace conventional face-to-face learning. The lack of infrastructure, curricula that are not designed for distance learning, and the characteristics of taxation learning that require practical work encourage the emergence of anxiety and dissatisfaction with tax distance learning. This study attempts to close the gap in previous research that has not empirically tested gender and grade differences in taxation distance learning under uncertain conditions. In addition, this study aims to examine the direct effect of anxiety on taxation distance learning satisfaction. Primary data was obtained through an online survey and processed using SPSS 25. A total of 469 tax undergraduate students were the research sample identified using purposive sampling. The ANOVA and Independent sample t-test revealed that there was no difference between tax distance learning anxiety and tax distance learning satisfaction based on gender and grade. However, this study confirmed that anxiety had a negative effect on tax students' satisfaction with distance learning during the Covid-19 pandemic.